Europe's voting space and the problem of second-order elections: A transnational proposal. (March 2016) - Bright, Jonathan; Garzia, Diego; Lacey, Joseph; Trechsel, Alexander
This article offers an empirically driven critical consideration of the idea of transnationalising Europe's voting space, which would mean allowing European citizens to vote for a party from any member state at the European Parliament elections. We argue that such a move would reduce the second-order problem in European elections, as it would force political parties to move away from campaigning solely on national issues. We also claim that it would improve the extent to which Europeans are represented in their parliament and would be particularly welcomed by citizens currently dissatisfied with the state of their national democracy. We offer evidence to back up these claims, based on data on the political preferences of almost half a million Europeans and 274 European parties.